Edukasi Aktivitas Fisik Pada Anak Usia Sekolah Dasar - Yadi Jayadilaga; Meliana Handayani; A. Ulfiana Fitri; Nurul Fajriah Istiqamah; Dian Anggraeni Rachman; Idhar Darlis; Sri Rezkiani Kas (Program Studi Manajemen FEB UNM, 2023)
This activity aims to provide information about the importance of physical activity in children and the long-term benefits to health if done correctly. Childhood is an important period for developing movement skills and learning healthy living habits as a basis for lifelong health and well-being. Lentera Kasih school students become partners in this independent service. Location of independent service activities on the grounds of Lentera Kasih School, Makassar. The activity will be held on August 12, 2023. The children's activity stages involve aerobic, muscle, and bone strengthening. The conclusion about the service activities is that the children are enthusiastic enough to participate. Physical activity in children is directed to follow daily play patterns so that boredom does not appear in children.